ANALISIS PERKEMBANGAN BAHASA ANAK USIA SEKOLAH DASAR: KAJIAN TEORITIS DAN IMPLIKASINYA DALAM PEMBELAJARAN - Eko Kuntarto; Nabila Anastasya; Na’imahtul Zakiyah Dwi Wardhani; Ifdah Aulia; Muhammad Sholeh (STKIP Subang, 2024)
This study examines the application of Lev Vygotsky's theory, particularly the concepts of Zone of Proximal Development (ZPD) and scaffolding, in language learning in early elementary school classes. Language skills are a crucial aspect of children's cognitive development, with social interaction playing a key role in the learning process. A qualitative research method was employed, involving first and second-grade students and language teachers as subjects. Data were collected through observations, interviews, document analysis, and questionnaires. The findings indicate that the implementation of ZPD and scaffolding effectively enhances children's language skills, increases motivation, and strengthens social interactions. Teachers act as scaffolders, providing appropriate support to help students learn. In conclusion, applying Vygotsky's theory in language learning in early elementary education can bolster children's language abilities, build confidence, and support social development.